2005
DOI: 10.1099/mic.0.27487-0
|View full text |Cite
|
Sign up to set email alerts
|

Flanking direct repeats of hisG alter URA3 marker expression at the HWP1 locus of Candida albicans

Abstract: HWP1 encodes an adhesin of Candida albicans and has been implicated in filamentation and virulence. URA3, an often-used transformation selection marker, is apparently incorrectly expressed when integrated at the HWP1 locus, which results in an attenuated virulence phenotype. Expression of URA3 is compromised by ectopic integration at other loci as well. In contrast, prior studies from the authors' laboratory had demonstrated that the filamentation deficiency and attenuated virulence of hwp1D mutants were fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
3
36
1
Order By: Relevance
“…Proper expression of C. albicans URA3 (orf19.1716 ) is important for virulence and for dimorphic transition (Lay et al 1998;Brand et al 2004;Sharkey et al 2005). As such, phenotypic assays often compare Uri + versions of mutants, which have been constructed in a CAI4 background, to CAF2-1 (URA3/ura3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper expression of C. albicans URA3 (orf19.1716 ) is important for virulence and for dimorphic transition (Lay et al 1998;Brand et al 2004;Sharkey et al 2005). As such, phenotypic assays often compare Uri + versions of mutants, which have been constructed in a CAI4 background, to CAF2-1 (URA3/ura3).…”
Section: Resultsmentioning
confidence: 99%
“…Relevant to this work is a short region of Chr3R nearby CEN3 that homozygosed during the construction of CAI4 (ura3D/ura3D) from CAF2-1 (ura3D/URA3). Phenotypic analysis of mutants derived from CAI4 is complicated because URA3 expression levels affect filamentation and virulence properties (Bain et al 2001;Chen et al 2004;Noble and Johnson 2005;Sharkey et al 2005;Noble et al 2010) as well as replication stress (Poulter 1990). Yet we found that, (1) URA3 reintegration into its endogenous locus does not affect MMS sensitivity and (2) supplementing YPD with additional uridine did not modify MMS sensitivity (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm had few hyphae, while both planktonic yeast cells and hyphae were in the surrounding medium. Several years ago, a study showed that the deletion of HWP1 does not cause a filamentation defect (347). Biofilms formed when bcr1⌬/⌬ mutant cells were mixed in various ratios with cells of strains with wild-type HWP1 or with heterozygous or homozygous null mutations (277).…”
Section: Adhesinsmentioning
confidence: 99%
“…The most widely used marker is the URA3 gene, which encodes orotidine-5Ј-phosphate decarboxylase and confers uracil prototrophy. However, this marker must be used with caution; URA3 expression levels can affect virulence and are susceptible to chromosome position effects, thereby complicating the analysis of strains constructed with URA3 as a selectable marker (62,261,281,292). To avoid the use of the URA3 marker, various other auxotrophic markers, as well as dominant markers, have been developed and are currently used (206,224,241,263).…”
Section: Genetic Manipulation With C Albicansmentioning
confidence: 99%